2016
DOI: 10.1105/tpc.15.00626
|View full text |Cite
|
Sign up to set email alerts
|

Aspartyl Protease-Mediated Cleavage of BAG6 Is Necessary for Autophagy and Fungal Resistance in Plants

Abstract: The Bcl-2-associated athanogene (BAG) family is an evolutionarily conserved group of cochaperones that modulate numerous cellular processes. Previously we found that Arabidopsis thaliana BAG6 is required for basal immunity against the fungal phytopathogen Botrytis cinerea. However, the mechanisms by which BAG6 controls immunity are obscure. Here, we address this important question by determining the molecular mechanisms responsible for BAG6-mediated basal resistance. We show that Arabidopsis BAG6 is cleaved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
138
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(141 citation statements)
references
References 61 publications
2
138
1
Order By: Relevance
“…Plant cells also employ autophagy to defend themselves against several pathogens (Han et al, 2011; Li et al, 2016). Autophagy positively regulates plant resistance against necrotrophic pathogens (Lai et al, 2011; Lenz et al, 2011; Kabbage et al, 2013) but negatively affects plant resistance against the biotrophic pathogen powdery mildew (Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Plant cells also employ autophagy to defend themselves against several pathogens (Han et al, 2011; Li et al, 2016). Autophagy positively regulates plant resistance against necrotrophic pathogens (Lai et al, 2011; Lenz et al, 2011; Kabbage et al, 2013) but negatively affects plant resistance against the biotrophic pathogen powdery mildew (Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Arabidopsis thaliana provides an example of the opposite role of limited proteolysis: activation of autophagy and switching of cellular stress response from death to survival (Li et al, 2016). The authors have shown that cleavage of the plant Bcl2-associated athanogene 6 (BAG6) by aspartyl protease APCB1 induces formation of autophagosomes in plants ( Fig.…”
Section: Proteolysis In the Early Stages Of The Autophagy Pathwaymentioning
confidence: 99%
“…However, most reported plant aspartic proteases induce PCD, such as NtCDN41, nucellin, OsS5, AtCDR1, OsAP25/37, and APCB1 (Chen and Foolad, 1997;Xia et al, 2004;Kato et al, 2005;Chen et al, 2008;Niu et al, 2013;Li et al, 2016). These findings suggest that plant aspartic proteases have different, even contrary, functions in PCD, which may be due to the specific substrates of these aspartic proteases in different tissues or cell types.…”
Section: A36 and A39 Play Vital Roles In Pollen And Ovule Developmentmentioning
confidence: 99%